(3dWGFa CNHGQ GdChd ajef JUQa aj eUQ ef CQHGH GdOhds - (3GdESMGbj , eMeO Hf YHO GdeYWj Hf CHj GdaJM Hf CMeO Hf YHO GdeZfj Gdefhaj,J (B1060 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdYRjR aj edcg hdGbJOGQg , GdPj edc GdhLhO hChLOg HEQGOJg hdGbJOGQg s
(3BNQgG (B:s
(3Hedjc aGb cSQi EP dg Gdedc GdYXje CHbg aj GdPcQ jJdi jG Mcje s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B247 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B254s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B357 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs